PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi pada PT. Pos Indonesia Cabang Pekalongan) - Rizky Aditama, 13.05.51.0166; Murdiyanto, Agus (Students' Journal of Economic and Management, 2018)
The purpose of this research is to find out and to examine the influence of leadership style, motivation, and compensation to the employees performance on PT Pos Indonesia Cabang Pekalongan. The population is the employees on PT Pos Indonesia Cabang Pekalongan and tha smples are 100 respondents.The multiple linear regressions analysis to test variable influence leadership style, motivation, and compensation to partial on performance employees.Test hypothesis suggest that leadership style has positive effect and significant against employees performance. Motivation has positive effect and significant against employees performance. Compensation has positive effect and significant against employees performance PT Pos Indonesia Cabang Pekalongan. Keywords : Leadership Style, Motivation, Compensation, Performance